The Effect Of E-Commerce Trust, Site Loyalty, And E-Commerce Satisfaction On Purchasing Behavior - Agung Maulana; Idrus Kurniawan; Angga Riyansyah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
As the digital world progresses, consumers become more confident in the social environment influencing their purchase decisions. Additionally, there are new possibilities for entrepreneurs to use social commerce to boost sales. While Trust has been investigated, most studies have focused on digital trusts, such as the reliability of user evaluations. There are several factors to consider while examining consumer behavior and gaining insight into customer decision-making. The project's ultimate goal is to provide a trustworthy and dependable framework for online business. The outcomes of this study were deemed satisfactory in that they provided insight into how to maximize customer satisfaction and Loyalty with an e-Commerce site (which ultimately influences consumers' purchasing decisions). This study demonstrates that the faith customers have in online reviews and the importance of social commerce significantly impact the degree to which customers are satisfied with and loyal to marketplaces.